The Religious Moderation Education: Implementing the Nusantara Islamic Curriculum at Tulang Bawang Islamic Boarding School - M. Afifuddin; Suhono Suhono (Bulletin of Science Education, 2025)
This study examines the implementation of the Nusantara Islamic curriculum in fostering religious moderation at Tulang Bawang Islamic Boarding School. Using a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the Nusantara Islamic curriculum effectively integrates Islamic values with national principles, thereby promoting inclusive attitudes, tolerance, and respect for diversity among students. Furthermore, the curriculum contributes to the strengthening of social harmony through learning practices grounded in local wisdom. This study contributes theoretically by enriching the discourse on religious moderation education within Islamic boarding schools and practically by providing an empirical model for curriculum development that aligns Islamic values with national identity and multicultural realities in Indonesia. This research is expected to serve as a reference for the development of Islamic boarding school curricula that are responsive to the challenges of the Indonesian context and globalization.